ARTIFICIAL INTELLIGENCE AS A LANGUAGE LEARNING PARTNER - Bekchanova Mahliyoxon Hamidjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract:The rapid advancement of artificial intelligence (AI) has transformed various aspects of modern society, particularly the field of education. Language learning, which traditionally relied on textbooks, classroom instruction, and face-to- face interaction, is now increasingly supported by intelligent technologies. AI-powered applications, chatbots, virtual assistants, adaptive learning platforms, and automated assessment systems have become effective tools for language acquisition. These technologies provide learners with personalized learning experiences, immediate feedback, continuous practice opportunities, and access to authentic language resources. As a result, artificial intelligence is no longer viewed merely as a technological innovation but as an active learning partner that supports students throughout their educational journey. Students can practice speaking, listening, reading, and writing skills through interactive digital environments that adapt to their individual needs and proficiency levels. This article examines the role of artificial intelligence as a language learning partner, discussing its advantages, challenges, and implications for the future of language education.